CIVIC CULTURE AS VALUE NORMATIVE BASE CIVIL SOCIETY’S FORMATION - Жеребятнікова, І.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
The article is devoted to some aspects of phenomenon of civic culture in development of civil society. The author analyses the nature, main features and specific character of manifestation of civic culture in the system of social and political attitude. The problem of its formation in the conditions of the modern Ukrainian society is researched. It is well-proven that a civic culture is the important factor of building of the democratic, legal, social state.